Expansion of Police Power In Public Schools and the Vanishing Rights of Students - Beger, Randall R. (Social justice, 2002)
Law enforcement expansion in U.S. schools and the vanishing Fourth Amendment rights of public school children are examined. It is explained that the climate of fear generated by school shootings has spurred public school administrators to increase security through physical means and to hire more police and security guards. Furthermore, it the manner in which courts are granting police and school officials more authority to conduct searches of students is described.